The impact of political connections on the level of cash holdings: evidence from Tunisian listed firms. (17th November 2021) - Goucha, Nadia Ben Sedrine; Boubacar, Inoussa; Loukil, Nadia
In this empirical study, we examine the relationship between political connections and corporate cash policy in Tunisia. Undoubtedly, politically connected firms gain a variety of economic benefits ranging from the allocation of government contracts to favourable credit terms. In general, politically connected firms are less financially constrained and do not have an incentive to hold liquidity. Therefore, political connections exert a substitution effect on the firm's cash holdings. From the agency perspective, firms with political ties hold more cash than other firms, and their managers have access to money they can use for lucrative perk projects. Through examining the business data of several Tunisian firms 2008-2014, we review the theoretical motives for cash holding by politically connected firms and provide statistical evidence on the substitution effect of political connections on cash holdings. The result confirms a strong statistical relation between the level of cash-holding and political connection. The policy implication of our paper is that political relationships can shape corporate financial decisions.